2020
DOI: 10.1177/0021998320915952
|View full text |Cite
|
Sign up to set email alerts
|

Low velocity impact and fracture characterization of SiO2 nanoparticles filled basalt fiber reinforced composite tubes

Abstract: Nano-microscale fracture mechanisms, which affect fracture toughness, play an important role in improving the impact characterization of fiber reinforced polymer composites. Therefore, crack behaviors are tried to be controlled with fracture mechanisms by filling nanoparticles into polymer matrix for improving impact characteristics and fracture toughness in latest studies. In this study, it was aimed to investigate the effects of SiO2 nanoparticles addition into epoxy matrix on the low velocity impact charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 65 publications
(252 reference statements)
0
29
0
Order By: Relevance
“…It was thought to be a sign from the decreases of displacements that the local bending and contact stiffness increased by filling nanoparticles for both 10 J and 20 J of energy levels. 15,30 In addition the amount of failures and failure propagations were restricted by filling nanoparticles. 26,33 The failures were investigated with failure analysis in detail.…”
Section: Low Velocity Impact Testsmentioning
confidence: 99%
See 3 more Smart Citations
“…It was thought to be a sign from the decreases of displacements that the local bending and contact stiffness increased by filling nanoparticles for both 10 J and 20 J of energy levels. 15,30 In addition the amount of failures and failure propagations were restricted by filling nanoparticles. 26,33 The failures were investigated with failure analysis in detail.…”
Section: Low Velocity Impact Testsmentioning
confidence: 99%
“…The lower bending rigidity may be the sing of the large amounts of failures and absorbed impact energies. 6,15,21,34,[37][38][39][40][41][42][43] Microscope and SEM analysis When damage behaviors of SiO 2 /BFR/Epoxy composites were observed at 10 J energy level given in ( Figure 5(a)), a small amount of local debonding damages was detected in the microscope image of cross section where cut from impacted zone of it. It was observed that debonding damages occurred in the upper layers.…”
Section: Low Velocity Impact Testsmentioning
confidence: 99%
See 2 more Smart Citations
“…A certain part of these researches has been devoted to the mechanical properties of composite pipes and especially focused on filament wound composite pipes. The most common properties investigated are burst performance [14,15], tensile and compressive characteristics [16][17][18][19], fatigue behavior [20][21][22] and impact response [23][24][25]. Gemi et al [26] analyzed the effects of various drill types on drilling performance of glass fiber-reinforced composite pipes.…”
Section: Introductionmentioning
confidence: 99%